Principles of comparative politics - Mahler, Gregory S. (Pearson, 2013)
Debuting in its first edition, Principles of Comparative Politics emphasizes the analysis of institutions, giving readers an accessible and concrete cross-national introduction to the political world. Surveying themes and countries,this brief text lays out the major elements of a political system-executive, legislature, political behavior, and more-and examines them in Britain, France, Germany, Russia, Mexico, China, Kenya, and Canada. Principles of Comparative Politics helps readers understand the mechanisms that drive politics and appreciate the variations among them.